2017
DOI: 10.1002/2016gb005472
|View full text |Cite
|
Sign up to set email alerts
|

A global estimate of the full oceanic 13C Suess effect since the preindustrial

Abstract: We present the first estimate of the full global ocean 13 C Suess effect since preindustrial times, based on observations. This has been derived by first using the method of Olsen and Ninnemann (2010) to calculate 13 C Suess effect estimates on sections spanning the world ocean, which were next mapped on a global 1°× 1°grid. We find a strong 13 C Suess effect in the upper 1000 m of all basins, with strongest decrease in the subtropical gyres of the Northern Hemisphere, where δ 13 C of dissolved inorganic carbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

17
141
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(170 citation statements)
references
References 92 publications
17
141
3
Order By: Relevance
“…The contribution of biology to the modelled δ 13 C distribution is generally below 45 % and has a steep gradient from the surface to the deep ocean. The (thermodynamic) fractionation effect of air-sea gas exchange on δ 13 C is strongly impeded by the long equilibration time of 13 C, which results in room for biological processes to contribute significantly to δ 13 C and Δδ 13 C (Eide et al, 2017a;Lynch-Stieglitz et al, 1995;Schmittner et al, 2013). In the deep ocean below 250m, the influence 25 of biology increases to 35-45 % due to the remineralisation of POC, with the exception of the Arctic Ocean where no POC production is modelled due to the sea ice cover ( Fig.…”
Section: Air-sea Gas Exchange Versus Biologymentioning
confidence: 99%
“…The contribution of biology to the modelled δ 13 C distribution is generally below 45 % and has a steep gradient from the surface to the deep ocean. The (thermodynamic) fractionation effect of air-sea gas exchange on δ 13 C is strongly impeded by the long equilibration time of 13 C, which results in room for biological processes to contribute significantly to δ 13 C and Δδ 13 C (Eide et al, 2017a;Lynch-Stieglitz et al, 1995;Schmittner et al, 2013). In the deep ocean below 250m, the influence 25 of biology increases to 35-45 % due to the remineralisation of POC, with the exception of the Arctic Ocean where no POC production is modelled due to the sea ice cover ( Fig.…”
Section: Air-sea Gas Exchange Versus Biologymentioning
confidence: 99%
“…C decrease between the preindustrial and modern period observed in the North Atlantic (Eide et al, 2017). …”
mentioning
confidence: 98%
“…C for the effects of industrial emissions (the "Suess" effect) and bomb radiocarbon in the atmosphere using published estimates (Broecker et al, 1980;Key, 2001;Sabine et al, 2004;Eide et al, 2017). For example, Eide et al (2017) establishes a mathematical relationship between Suess δ 13 C and CFC-12 in the ocean, which we applied using GLODAP CFC-12 data to correct the ocean δ 13 C data.…”
mentioning
confidence: 99%
“…For example, Eide et al (2017) establishes a mathematical relationship between Suess δ 13 C and CFC-12 in the ocean, which we applied using GLODAP CFC-12 data to correct the ocean δ 13 C data. We force the model with late Holocene average data for atmosphere CO 2 , δ 13 C and ∆ 14 C (data sources in Table 1).…”
mentioning
confidence: 99%
See 1 more Smart Citation